Arrival and Price Behaviour of Major Mustard Markets in Haryana - Bhatia, Jitender Kumar; Bishnoi, Dalip Kumar; Dhingra, Atul; Nimbrayan, Parveen Kumar (Indian Journal of Extension Education, 2022)
The market arrival and price behaviour of major mustard markets in Haryana during the pre-e-NAM (2010-2016) and post-e-NAM (2017-2021) periods was studied. In Haryana, e-NAM was implemented in 2016 but after adoption, its impact was shown in 2017. Results revealed that arrivals of mustard increased during pre e-NAM period in two selected markets, whereas, prices of mustard were found to be increased in Sirsa market while it decreased in Rewari market. In post e-NAM period, arrival and prices of mustard found to be decreased in both the markets. It was found that adoption and awareness about e- NAM was found higher in case of Sirsa market as compared to the Rewari market. Both Sirsa and Rewari markets were found spatially integrated in both pre as well as post e- NAM period. The Granger causality test in the post-e-NAM period demonstrated that mustard prices in Sirsa market were having a unidirectional causation on the prices in Rewari market, however there was no causality link between mustard prices in both markets in the pre-e-NAM time.